2018
DOI: 10.1002/cam4.1872
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, stage distribution, and relative roles of surgery and radiotherapy on survival of persons with primary prostate sarcomas

Abstract: BackgroundPrimary prostate sarcomas (PPS) are rare. Outcomes for this cancer have not been well characterized.Materials and MethodsSubjects with a PPS diagnosed between 1973 and 2014 were identified in the SEER database. Subjects were stratified by disease stage and types of therapies received. Disease‐specific survival (DSS) and Overall survival (OS) was estimated by Kaplan‐Meier analysis and cohorts were compared with a univariate and multivariable Cox regression.ResultsThe incidence of PPS among all prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Prior studies investigating rhabdomyosarcoma demographics and prognostic factors using databases have largely focused on specific anatomic sites or subtypes . In a 2017 study by Nasioudis et al rhadomyosarcoma of the lower female genital tract was shown to be most prevalent in prepubertal girls and adolescents, but carry excellent survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies investigating rhabdomyosarcoma demographics and prognostic factors using databases have largely focused on specific anatomic sites or subtypes . In a 2017 study by Nasioudis et al rhadomyosarcoma of the lower female genital tract was shown to be most prevalent in prepubertal girls and adolescents, but carry excellent survival rates.…”
Section: Discussionmentioning
confidence: 99%